Crowdfunding in the Context of Public Policies of Brazilian Science, Technology and Innovation - Silva, Elaine da; Hassem, Alina (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2019)
This article aims to analyze the impact that crowdfunding can have on Brazil 's innovative activity, and how governmental innovation policies approach the theme. For that, an analysis of governmental policies for Science, Technology and Innovation in Brazil regarding the financing modalities of the innovative activity, in particular crowdfunding, is presented. For the analysis of the data we opted for the application of the content analysis method. The results show that the policies analyzed focus on financing by governmental agencies, therefore other financing modalities, especially crowdfunding, can be better exploited.